Digital Marketing: Tools, Trends and Perspectives - Iryna Polishchuk; Yuriy Dovhan; Oksana Yakushevska; Larysa Dovhan; Oksana Kravchenko; Viktoriia Petrova (Proceedings of the International Conference on Applied Innovations in IT, 2025)
The article highlights the issues of modern marketing-oriented business response to new challenges associated with the rapid development of information and digital technologies and digitalization of the population. The purpose of the article is to highlight the results of researchers' approaches to understanding and content of digital marketing, reviewing its modern tools, trends, and prospects. Comparative, institutional, systemic, and structural-functional methods are used to conduct the research. The theoretical aspects of the application of marketing tools and the history of the emergence of digital marketing are briefly highlighted, the differences between traditional and digital marketing are identified. The researchers' approaches to understanding the content of digital marketing, its components, and its tools are reviewed. The key characteristics of digital marketing are identified. The main digital marketing tools that are currently used are described. Modern trends in their application are given. The possibilities of further development and prospects for the application of digital marketing tools in the near and more distant future are identified. It is emphasized that traditional marketing management support tools and marketing implementation tools are naturally transforming and becoming digital. It was concluded that modern businesses adapt to the digital environment and actively use digital marketing tools to meet the demands, maintain competitiveness, and achieve success.